Dental Tourism: Exploring Foreign Patients' Motivation for Choosing Aligner Treatment in Indonesia - Gede Anita Adi Prstiwi, Ni Luh; Ketut Lasmini, Ni; Nengah Wirsa, I; Nyoman Sri Wisudawati, Ni (Yayasan Pendidikan Belajar Berdikari, 2025)
Technological advancements in orthodontics, particularly aligner treatment, have made teeth straightening more convenient, attracting individuals with active lifestyles. The rise of dental tourism has led foreign patients to seek aligner treatment in Indonesia due to cost savings, quality care, and the opportunity to combine treatment with travel. This study employs a qualitative phenomenological approach to explore the push and pull factors influencing patient decisions, using in-depth interviews, observations, and document analysis at a Bali dental clinic. Data were analyzed using NVivo 14, with verification techniques such as memsber checking, audit trails, and triangulation ensuring research validity. The word cloud analysis highlights key factors affecting foreign patients’ choices, including location, service quality, affordability, and digital promotions. Hierarchy charts reveal that perceptions of service, pre-treatment knowledge, treatment costs, and push-pull factors from home countries significantly impact decision-making, with affordability and positive experiences playing major roles. The project map emphasizes social media, particularly TikTok, as an essential marketing tool, alongside personalized care, flexible scheduling, and lower costs that attract patients from Australia, the UK, and Germany. Respondents highlighted the clarity of information provided by clinics, though some suggested improving English-language communication for better patient experiences. Indonesia’s combination of affordable pricing, high-quality service, and seamless patient experiences strengthens its position as a preferred destination for aligner treatment. As dental tourism continues to grow, optimizing marketing strategies and improving service quality will be crucial in maintaining Indonesia’s competitive edge in the global market.